The Effect of Pronunciation Variations on Students’ Speech Perception: A Psycholinguistic Study - Irene Zai; Arif Halawa; Muharni Zebua; Afore Tahir Harefa (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
Learners of English as a Foreign Language (EFL) are often exposed to pronunciation variances that could affect their perception and comprehension of spoken English. Variations in pronunciation, particularly in words that sound similar, frequently cause perceptual ambiguity and misunderstandings when listening. The purpose of this study is to investigate how learners perceive and adjust to various pronunciation forms, as well as how pronunciation differences affect students' perceptions of speech. This study employed a descriptive-interpretive approach within a psycholinguistic framework. The participants were English Education Study Program undergraduates who had previously studied the language. A hearing exercise with words with different pronunciations and a perceptual questionnaire intended to elicit students' experiences, opinions, and cognitive methods in processing spoken input were used to gather data. The results show that initial confusion and hesitancy in word recognition were driven by pronunciation variances, especially when there was little contextual assistance. But with repeated exposure, students showed that they could modify their perspective by referencing past hearing experiences. These findings imply that speech perception is a cognitive process that is both dynamic and experience-based. The study comes to the conclusion that including pronunciation differences into listening teaching will improve students' comprehension of spoken English in everyday communication and increase their perceptual flexibility.